1995
DOI: 10.1136/thx.50.11.1227
|View full text |Cite
|
Sign up to set email alerts
|

HIV related bronchiectasis.

Abstract: LETTERS TO THE EDITOR HIV related bronchiectasis In their review of new developments in pulmonary diseases affecting HIV infected individuals (March 1995;50:294-302) Mitchell and Miller do not discuss bronchiectasis. They mention indolent bronchopulmonary Pseudomonas aeruginosa infection comparable to that seen in cystic fibrosis, but do not comment on bronchiectasis which is now well described in adults and children with HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…With the application of antibiotics, genetic diseases such as cystic fibrosis of the lung, immunodeficiency disease and disorders of cilia movement were becoming the general causes of bronchiectasis [ 41 ]. NTM infections and α 1 -antitrypsin deficiency syndrome were all predisposing factors [ 42 ] which led to bronchiectasis becoming one of the potential factors in AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…With the application of antibiotics, genetic diseases such as cystic fibrosis of the lung, immunodeficiency disease and disorders of cilia movement were becoming the general causes of bronchiectasis [ 41 ]. NTM infections and α 1 -antitrypsin deficiency syndrome were all predisposing factors [ 42 ] which led to bronchiectasis becoming one of the potential factors in AIDS.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Moreover, several studies have shown a higher-than-expected rate of bronchiectasis in persons living with HIV. 11 – 13 The association is not surprising as recurrent and/or severe airway infections are risk factors for the development of bronchiectasis, and even otherwise healthy individuals living with HIV have much higher rates of acute bronchitis and bacterial pneumonia than the general population.…”
Section: Part 1: Hiv-associated Airway Diseasesmentioning
confidence: 99%
“…9 Out of the very few studies reporting cases of bronchiectasis in HIV infected individuals, the prevalence ranged from 15 to 42%. [10][11][12][13][14][15][16] )ROORZLQJ WKH ¿UVW FDVH UHSRUW IURP 2[IRUG LQ 1992, 10 there are very few cases of HIV reported to have bronchiectasis although the prevalence of bronchiectasis is higher in HIV infected population. This might be because of the low index of suspicion and because of the fact that the easily available investigations like chest radiographs in WKH HDUO\ VWDJHV PD\ EH QRUPDO RU QRQVSHFL¿F Here we are reporting the case of bronchiectasis in HIV infected 7 years old child.…”
Section: Introductionmentioning
confidence: 99%